Determination of the optimum number of water meter test flow rates in South Africa - Ncube, Mthokozisi; Sibanda, Fahlani; Ilemobade, Adesola A. (Aqua (London, England), 2024)
Metering errors are one of the main contributors of apparent losses, therefore the determination of the optimum number of flow rates to reproduce the meter error curve is of critical importance. The objective of this study was to determine the optimum number of flow rates suitable for testing water meters in South Africa. This was achieved by accessing data from two local studies that tested 323 used water meters over 10 flow rates. The used water meters had been removed from the field and tested in the laboratory. The data from the laboratory tests were then further analysed by recalculating the weighted error for different flow rate combinations. The optimum number of flow rates, which was found to be 7, was the combination that minimised the weighted error of the tested meters. This study therefore recommends increasing the number of flow rates prescribed by the South African National Standard 1529-1:2019 from three flow rates (qmin, qt and qp) to 7 flow rates, namely 7, 15, 30, 60, 120, 1500 and 3,000 l/h.